Safety profile of lenalidomide in patients with lower-risk myelodysplastic syndromes without del(5q): results of a phase 3 trial - Almeida, Antonio; Fenaux, Pierre; Garcia-Manero, Guillermo; Goldberg, Stuart L; Gröpper, Stefanie; Jonasova, Anna; Vey, Norbert; Castaneda, Carmen; Zhong, Jianhua; Beach, C L; Santini, Valeria (Leukemia & lymphoma, 2018)
UNLABELLED: The safety profile of lenalidomide use in lower-risk myelodysplastic syndromes (MDS) patients with del(5q) is well-established, but less is known in non-del(5q) patients. We provide safety data from a randomized, phase 3 trial evaluating lenalidomide in 239 patients with lower-risk non-del(5q) MDS ineligible/refractory to erythropoiesis-stimulating agents (ESAs). Compared with placebo, lenalidomide was associated with a higher incidence of grade 3-4 treatment-emergent adverse events (TEAEs; 86% vs. 44%), but not risk of infection (p = .817) or hemorrhagic events (p = 1.000). Grade 3-4 non-hematologic TEAEs were rare (the incidence of grade 3-4 pneumonia, e.g. was 5.6% in the lenalidomide group and 2.5% in the placebo group). Common grade 1-2 non-hematologic TEAEs did not require dose modifications or treatment discontinuation. Acute myeloid leukemia and second primary malignancies incidence was similar across treatment groups. Lenalidomide had a predictable and manageable safety profile in lower-risk non-del(5q) MDS patients ineligible/refractory to ESAs. Guidance on managing lenalidomide-related TEAEs is provided to help maintain patients on therapy to achieve maximum clinical benefit. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT01029262.
Keywords: průjem; Humans; lidé středního věku; Spasm; Neutropenia; Female; rizikové faktory; Aged; dospělí; Diarrhea; senioři; lidé; exantém; Fatigue; myelodysplastické syndromy; Adult; Lenalidomide; imunologické faktory; Chromosomes, Human, Pair 5; immunotherapy; ženské pohlaví; lidské chromozomy, pár 5; Male; chromozomální delece; Chromosome Deletion; Middle Aged; Aged, 80 and over; únava; Immunologic Factors; neutropenie; senioři nad 80 let; Myeloid leukemias and dysplasias; Myelodysplastic Syndromes; mužské pohlaví; lenalidomid; manipulation of the immune response; Exanthema; spasmus; Risk Factors